2003
DOI: 10.4102/sajp.v59i4.206
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the magnitude of force applied by students when learning a mobilisation technique

Abstract: Passive accessory intervertebral movements (PAIVM’s) are frequently used by physiotherapists in the  assessment and management of patients. Studies investigating the reliability of passive mobilisation techniques have shown conflicting results. Therefore, standardisation of PAIVM’s is essential for research and teaching purposes, which could result in better clinical management. In order to standardise graded passive mobilisation techniques, a reliable, easy-to-use, objective measurement tool must be used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 2 publications
(6 reference statements)
0
27
0
Order By: Relevance
“…Four studies reported PA mobilization forces applied to the cervical spine [22][23][24][25] (Table 3). In all studies, mobilization forces applied to the cervical spine tended to be somewhat lower than mobilization forces applied to the lumbar or thoracic spines.…”
Section: Quantification Of Mobilization Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported PA mobilization forces applied to the cervical spine [22][23][24][25] (Table 3). In all studies, mobilization forces applied to the cervical spine tended to be somewhat lower than mobilization forces applied to the lumbar or thoracic spines.…”
Section: Quantification Of Mobilization Forcesmentioning
confidence: 99%
“…Both studies reported grade I PA mobilization forces. 23,24 The recorded forces ranged from approximately 0.1 to 5 N (converted from original data, 11-500 g, with the assumption that force was applied in a smooth continuous manner as would be expected for a grade I mobilization). However, the flexible force transducer used in these 2 studies had a maximum limit of 500 g and 15% of the participants in 1 study (student physiotherapists) exceeded its capacity, resulting in loss of data.…”
Section: Issues When Comparing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In contrast, other studies of cervical mobilization forces applied to asymptomatic persons report that students applied significantly higher forces for grade I and II mobilizations than therapists 17 or more experienced students. 27 In the lumbar spine, students also applied greater force for a grade II central PA mobilization prior to formal feedback on their forces. 18 A possible reason for these differences between therapists' and students' forces may be the way each group was taught to apply mobilization.…”
Section: Mean Peak Forcementioning
confidence: 99%
“…Similar sensors have been used in research on prosthetics, ergonomics, and physical medicine. 15,16 This study compared results (strong/weak) between short (1 second) and long (3 seconds) MMTs of the same subject. The null hypothesis was good agreement between long-and short-duration muscle tests, in other words, that the duration of the test would not influence the outcome.…”
Section: Introductionmentioning
confidence: 99%